Implementing Problem-Based Learning in Marketing Education: A Systematic Review and Analysis - Rosário, Albérico Travassos; Dias, Joana Carmo (Education sciences, 2024)
The marketing industry is rapidly evolving, prompting educational programs to adapt and provide graduates with relevant skills and knowledge. This systematic literature review and bibliometric analysis (SLRBA) explores the incorporation of problem-based learning (PBL) in marketing education. PBL is a teaching approach that encourages students to solve real-world problems by integrating theory and practice, thereby improving their critical thinking and decision-making skills. Our review synthesizes data from 71 sources, detailing the definition of PBL, strategies for its implementation in marketing education, and the associated benefits and challenges. The findings show that PBL enhances student engagement, provides hands-on experience, and equips students for real-world marketing challenges. Effective strategies for PBL adoption include leveraging social media, serious games, E-learning, and feedback systems to facilitate active learning and student participation. However, PBL poses challenges, such as high resource requirements, student resistance, and concerns over information accuracy. This review underscores the importance of PBL in closing the gap between theoretical concepts and practical skills, helping marketing students better meet industry expectations. The paper concludes with suggestions for future research and best practices for integrating PBL in marketing education.